Country Economic Memorandum for Sao Tome and Principe - Background Note 8 : How to Increase the Availability of Financing Needed to Stimulate Private Sector Investment? A Review of the State of and Barriers to Access to Financial Services in São Tomé and Príncipe - Barreto, Rúben; Vicente, Carlos Leonardo (World Bank, Washington, DC, 2019)
This note discusses the current structure of the financial sector in São Tomé and Príncipe (STP) and the main obstacles preventing mobilization and allocation of more resources to private sector investment. Since 2012, credit to the private sector in STP has been declining and is currently below peers. In an economy dominated by informality, banks provide credit to a limited number of borrowers, prioritizing large borrowers. A survey completed in 2017 showed that only 18 percent of micro, small and medium-sized enterprises (MSMEs) reported being registered and having a bank account, of which only 3 percent had access to credit. The same survey showed that only 39 percent of individuals, some of them owners of micro-enterprises registered under their personal name, have access to financial services. The note is divided into four sections. The first provides an overview of STP’s financial sector, analyzing and benchmarking its structure, depth, and soundness. The second section analyzes the landscape of access to financial services (focusing on individuals and MSMEs), while the third describes some of the key limitations of the financial infrastructure in STP that create obstacles to financial sector development and access to finance. Finally, the fourth section concludes with policy recommendations that can help increase access to financial services in STP.